The Relationship Between the Use of Medicinal Plants and Medication Adherence in the Elderly with Chronic Diseases - Hamid Reza Koohestani; Nayereh Baghcheghi (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Many older patients use medicinal plants, assuming that they are safe and without side effects. The present study aims to investigate the relationship between the use of medicinal plants and medication adherence in the elderly patients with chronic diseases. Methods & Materials In this descriptive cross-sectional study, 358 patients aged ≥60 years with chronic diseases were selected by a convenience sampling method. Data collection instrument was a three-part questionnaire assessing demographic information, history of using medicinal plants, and medication adherence using the Morisky medication adherence scale (MMAS). The data were entered into SPSS v.21 and analyzed using one-way analysis of variance, Chi-square test, independent t-test and logistic regression. Results The mean age of participants was 69.44±8.13 years and 52.23% were female. The majority of them were married (87.68%) with a junior high school education (71.64%).The overall mean score of MMAS was 5.48 (poor adherence). The percentage of patients with a history of taking medicinal plants in the last year with the prescription of physician was 41.34% (n=148) while the percentage of those used medicinal plants without the physician' prescription was 27.3% (n=98). The mean of MMAS score in the groups who used medicinal plants was lower than in the group with no history of using medicinal plants (P=0.001). The number of used medicinal plants, the frequency of using medicinal plants, and the duration of chronic disease had a statistically significant relationship with the medication adherence (P <0.05). Conclusion Due to the high consumption of medicinal plants in the elderly with chronic diseases and its relationship with poor medication adherence, it is necessary to educate them about the correct use of medicinal plants, their side effects, herb-drug interactions, the need to inform the doctor about use of medicinal plants, and adherence to medication.